Interface Properties in Binary Fluid Using Lattice Boltzmann Method - Li, Xiaoqi; Fang, Jichao; Ji, Bingyu (Frontiers in Earth Science, 2021)
Emulsified droplets coalescence and transport are of importance for oil production. Properties of emulsifiers are required to satisfy the stability of emulsion. Since experiments do not provide access to observables of interest. Numerical simulations with mesoscale scheme pose attractive method to gain insight into emulsifying stability, which is defined as a period of oil droplets movements at fixed ranges. A phase field based lattice Boltzmann model is used which simulate interface behavior. Various parameters including emulsified droplet size, interface thickness, viscosity ratio and density ratio have been discussed. The aim of this study is to provide a critical suggestion that predictive emulsifying behaviors of small oil droplets immersed in water environment.